Motivasi menjadi Guru Bimbingan dan Konseling (Studi Fenomenologi Terhadap Fresh Graduate) - Irawan, Andi Wahyu; Aswar, Aswar (IAIN Kudus, 2020)
Motivation to become a Guidance and Counseling Teacher (Phenomenology Study of Fresh Graduates): This study aims to find out the value of being a counseling guidance teacher at Senior High School in the city of Samarinda. The study used a qualitative approach with a phenomenological method. The research subjects were selected using purposive sampling in the criteria of fresh graduate and served as honorary teacher no more than one year, no more than 25 years old, and worked in a high school in the city of Samarinda. Data collected techniques were in-depth interviews and analyzed using Interpretative Phenomenological Analysis (IPA) techniques. The analysis technique sought to find meaning themes to become counseling guidance teachers. The results show three main themes, those are counseling guidance teachers interpreted as: 1) a soul calling; 2) to enjoy comfort; and 3) as a part-time job. The sub-theme of: 1) the soul calling is not profit oriented, realizing the future of students, and religious beliefs. The sub-theme of: 2) enjoy comfort that is a sense of comfort when students are helped, enjoy being parents for students, and to get life lessons. The sub-theme of: 3) part-time job is waiting to become civil servants and not easily laid off. Suggestion from this study are excepted to be a reference in helping counseling teachers in the process of valuing their work throught positive environmental conditioning to increase their productivity at work. Key Word: Fresh, Graduate, Work, Guidance, and Teacher